Evaluation of Antioxidant Activity and Growth Control Properties of Nonoscale Structure Produced from Aloe vera var. littoralis Extract on Clinical Isolates of Salmonella - Reza Ranjbar; Mohammad Arjomandzadegan; Hossein Hosseiny (MDPI AG, 2017)
The aim of the study was to examine antibacterial properties of microemulsion structure produced from Aloe vera var. littoralis extract as a new tool of nanoscale drug-like materials. Aloe vera var. littoralis (A. littoralis) extract was prepared by distillation method. A nonocarrier structure in the microemulsion system was prepared from the extract. Serial concentrations were prepared from 8 mg/mL extract and the nonocarrier containing 0.1 mg/mL pure extract and were evaluated by a disk diffusion method for 35 Salmonella clinical isolates. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by microbroth dilution assay using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) method by an enzyme-linked immunosorbent assay(ELISA) Microplate Reader apparatus. Antioxidant activity of the extract was determined by measuring the ferric reducing ability of plasma (FRAP) assay. From 35 clinical isolates of Salmonella, 17 isolates-including resistant isolates of S.E.1103 and S.E.49-had a zone of inhibition (ZI) of 7 to 32 mm in 0.007 mg/mL of the extract. S.E.76 isolate exposed to 30 µg/mL ceftazidime disk had a ZI of 12 mm but had 10 mm in 7µg/mL of A. littoralis extract. The inhibitory effect of a nanocarrier at a concentration of 25 µg/mL by 20 mm ZI was comparable by the ceftazidime (30 µg/mL) effect. MIC50 was 0.25 mg/mL and MBC50 was 0.5 mg/mL by MTT method for the extract. It was shown that A.littoralis extract had antioxidant activity of 31.67 µM/mg that could be increased based on concentration. It was concluded that the nanocarrier had a significant effect on the studied isolates in comparison with ordinary antibiotics and had potential for use as a natural antioxidant and antimicrobial material in complementary medicine.